2012
DOI: 10.1002/hed.23125
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of minimal‐incision thyroidectomy for Graves' disease: A prospective, single‐center study

Abstract: Background. The role of minimally invasive surgery in Graves' disease is still controversial. The aim of this study was to compare the clinical outcomes of patients undergoing minimal-incision thyroidectomy with those undergoing conventional thyroidectomy for Graves' disease. Methods. A prospective study was performed on 148 patients undergoing total thyroidectomy. Seventy-one patients underwent minimal-incision thyroidectomy and 77 underwent conventional thyroidectomy. Minimal-incision thyroidectomy was propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…9 Perigli et al reported mean postoperative hospital stay of 28.2±2 hours. 12 On the other hand, Ikeda et al reported that the patients remained hospitalized postoperatively for 4 days in their study. As regard to our results, we consider this is too long as we noticed no ill effect from the shorter postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…9 Perigli et al reported mean postoperative hospital stay of 28.2±2 hours. 12 On the other hand, Ikeda et al reported that the patients remained hospitalized postoperatively for 4 days in their study. As regard to our results, we consider this is too long as we noticed no ill effect from the shorter postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 82%
“…1 In study of Perigli et al the mean VAS scores (0-10) was 4.3±0.6 in 1 st group and 8.3±0.4 in 2 nd group. 12 In the study of Sywak et al the mean VAS scores (0-10) was 2.6 in 1 st group and 3.4 in 2 nd group. 14 In our study the mean satisfaction score as measured by NSS was 6.83±0.72 in 1 st group and 3.92±0.75 in 2 nd group with significant difference between both groups.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations